2019
DOI: 10.1017/s0022029919000372
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of grape marc in dairy cattle rations alters the bovine milk proteome

Abstract: Grape marc (GPM) is a viticulture by-product that is rich in secondary compounds, including condensed tannins (CT), and is used as a supplement in livestock feeding practices. The aim of this study was to determine whether feeding GPM to lactating dairy cows would alter the milk proteome through changes in nitrogen (N) partitioning. Ten lactating Holstein cows were fed a total mixed ration (TMR) top-dressed with either 1.5 kg dry matter (DM)/cow/day GPM (GPM group; n = 5) or 2.0 kg DM/cow/day of a 50:50 beet p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Further, the milk of dairy cows fed for three months with a diet containing 15% GP preserved the normal levels of fat, protein and caseins [22]. Finally, in a 4-week trial, dietary grape marc did not affect milk yield, milk protein or milk fat content of mid-lactation Holstein cows [40]. Overall, the present data further support the evidence that dietary GP does not alter milk yield or composition even after long-term supplementation.…”
Section: Discussionsupporting
confidence: 78%
“…Further, the milk of dairy cows fed for three months with a diet containing 15% GP preserved the normal levels of fat, protein and caseins [22]. Finally, in a 4-week trial, dietary grape marc did not affect milk yield, milk protein or milk fat content of mid-lactation Holstein cows [40]. Overall, the present data further support the evidence that dietary GP does not alter milk yield or composition even after long-term supplementation.…”
Section: Discussionsupporting
confidence: 78%
“…Some studies also reported the progeny of the animals such as primiparous (Safari et al ., 2018; Li et al ., 2021) and multiparous (Hausmann et al ., 2018; Safari et al ., 2018; Li et al ., 2021; Wang et al ., 2021) and included the period of lactation (Ianni et al ., 2019, 2021; Bonanno et al ., 2019b; Mapato et al ., 2021; Menci et al ., 2021) or specified mid-lactation (Scuderi et al ., 2019; Simitzis et al ., 2019). Design of the studies included randomized (Cais-Sokolińska et al ., 2015; Hausmann et al ., 2018; Safari et al ., 2018; Ianni et al ., 2019; Bonanno et al ., 2019a; Walkenhorst et al ., 2020; Li et al ., 2021; Wang et al ., 2021), stratified (Scuderi et al ., 2019; Walkenhorst et al ., 2020), allocated (Delgadillo-Puga et al ., 2019; Simitzis et al ., 2019) and 4 × 4 Latin square design with a 2 × 2 factorial arrangement (Mapato et al ., 2021). Dairy products evaluated in different studies included kefir (Cais-Sokolińska et al ., 2015), milk (all other papers) and, additionally, cheese (Ianni et al ., 2019; Bonanno et al ., 2019a, 2019b; Menci et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Peptides were separated using a gradient of 2.5-35% CH 3 CN/0.1% FA over 60 min, 35-100% CH 3 CN/0.1% FA in 1 min and then 100% CH 3 CN/0.1% FA for 4 min, followed by an immediate return to 2.5% CH 3 CN/0.1% FA and a hold at 2.5% CH 3 CN/0.1% FA. The nanospray and data acquisition methods were completed per Scuderi et al 39 . Briefly, samples were loaded onto a 100 μm × 500 mm capillary column packed with Halo C18 (2.7 μm particle size, 90 nm pore size, Michrom Bioresources, CA, USA) at a flow rate of 300 nL min −1 .…”
Section: Methodsmentioning
confidence: 99%